Simulating Stock Prices Using Geometric Brownian Motion: Evidence from Australian Companies - Krishna Reddy; Vaughan Clinton (Australasian Accounting, Business and Finance Journal, 2016)
This study uses the geometric Brownian motion (GBM) method to simulate stock price paths, and tests whether the simulated stock prices align with actual stock returns. The sample for this study was based on the large listed Australian companies listed on the S&P/ASX 50 Index. Daily stock price data was obtained from the Thomson One database over the period 1 January 2013 to 31 December 2014. The findings are slightly encouraging as results show that over all time horizons the chances of a stock price simulated using GBM moving in the same direction as real stock prices was a little greater than 50 percent. However, the results improved slightly when portfolios were formed.
Keywords: Geometric Brownian motion; Simulation; CAPM; Mean absolute percentage error (MAPE); Industry; Australia